Distinct methylated profiles in Helicobacter pylori dependent and independent gastric MALT lymphomas - Kaneko, Y (Copyright 2003 by Gut, 2003)
Background: Gastric mucosa associated lymphoid tissue (MALT) lymphomas are clinically subdivided into Helicobacter pylori dependent and independent, according to H pylori infection and the therapeutic course. In previous reports it has been suggested that H pylori independent cases develop from H pylori dependent cases, and sometimes transform into high grade diffuse large B cell lymphomas (DLBCLs). Methods: To better understand the pathogenesis of H pylori dependent and independent MALT lymphomas, we analysed the methylation profiles of eight independent CpG islands, including p15, p16, p73, hMLH1, death associated protein kinase, MINT1, MINT2, and MINT31 in H pylori dependent and independent MALT lymphomas, DLBCLs, and H pylori associated chronic gastritis. Results: We first confirmed that H pylori independent cases had a high incidence of t(11;18)(q21;q21) (4/8 cases) and aberrant BCL10 expression (7/8 cases) compared with H pylori dependent cases and gastric DLBCLs. In the methylation pattern study, all 13 H pylori dependent MALT lymphomas had more than four methylated loci while H pylori independent cases had less than two. According to the previous criterion, all H pylori dependent MALT lymphomas (13/13, 100%) and five of 10 (50%) DLBCLs were classified as CpG island methylator phenotype positive (CIMP+). In contrast, all H pylori independent MALT lymphomas were CIMP−. Conclusion: The distinct methylation pattern together with lack of chromosomal translocation in H pylori dependent MALT lymphomas suggest that H pylori dependent and independent MALT lymphomas have a different pathogenesis.